Decolonizing Diet: Healing by Reclaiming Traditional Indigenous Foodways - Bodirsky, Monica; Johnson, Jon (Cuizine)

(untitled) (McGill University Library, 2008)
AbstractTraditional Indigenous foodways remain important for the ongoing health and well being of contemporary Indigenous North American peoples. Drawing partly on primary research on food-related knowledge and experience within the First Nations community of Toronto, the authors trace how colonial policies of assimilation attempted to destroy Indigenous knowledge and in so doing spawned numerous trans-generational health consequences for Indigenous populations, which are still felt today. While colonial attempts at assimilation seriously undermined the integrity of traditional Indigenous foodways, today this cultural knowledge is undergoing a resurgence. Contemporary Indigenous peoples have expanded upon oral traditions with written stories of food gathering and recipes as a means to revitalize food knowledge, cultural integrity and community -- all inextricably linked to health. As such, the authors argue that fostering the resurgence of traditional Indigenous knowledge about food is a necessary in healing the trauma emerging from colonialism. Indigenous cookbooks provide opportunities to share information about traditional culture and food knowledge along with the recipes more conventionally associated with cookbooks.